Genome Sequences of Lactococcus garvieae TB25, Isolated from Italian Cheese, and Lactococcus garvieae LG9, Isolated from Italian Rainbow Trout - Ricci, Giovanni (American Society for Microbiology, 2012)
Lactococcus garvieae is a fish pathogen and an emerging zoonotic opportunistic pathogen as well as a component of natural microbiota in dairy products. Here, we present the first report of a genome sequence of L. garvieae TB25, isolated from a dairy source, and that of L. garvieae LG9, isolated from rainbow trout.